Heat-shrinkable laminated film and bag
By using the new polyester material and polyurethane buffer layer modified by nanotechnology in heat shrinkable laminated films, the problem of insufficient barrier performance of traditional laminated films when protecting sensitive and fragile products is solved, and more efficient protection is achieved Performance and extended shelf life.
Patent Information
- Application Number
- CN202411562422.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional heat shrinkable laminated films and bags have problems such as insufficient barrier properties and lack of buffer protection when protecting oxygen, water vapor-sensitive products and fragile items, resulting in a shorter shelf life of the product and a high probability of transportation damage.
Using a heat shrinkable laminated film composed of an outer protective layer, an intermediate barrier layer, an inner heat seal layer and a buffer layer. The intermediate barrier layer is layered with a new polyester material modified by nanotechnology and traditional polyethylene materials to buffer The layer is made of elastic polyurethane material to improve barrier and cushioning properties.
It significantly improves the protection performance of packaging contents, extends the shelf life, effectively prevents the penetration of oxygen and water vapor and external impact, provides good buffering protection for fragile items, and reduces the probability of damage during transportation and storage.
Smart Images

Figure CN119459082A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of packaging materials, in particular to a heat-shrinkable laminated film and a bag. Background Art
[0002] Heat-shrinkable laminated film is a plastic film with special properties. Under certain irradiation conditions, the molecular structure of this film will be transformed from the original linear chain structure to a three-dimensional network structure. This transformation causes changes in the physical and chemical properties of the plastic, making the film expand and elastic when heated to a certain temperature. Heat-shrinkable laminated film is usually designed for packaging, fixing and protecting various items. Its heat shrinkage properties enable it to fit tightly to the surface of the packaged items to form a protective layer, thereby effectively preventing the items from being damaged or contaminated during transportation or storage.
[0003] Heat shrinkable laminated bags are bags made of heat shrinkable laminated films. This type of bag not only inherits the excellent properties of heat shrinkable laminated films, such as heat shrinkage, transparency, tear resistance, etc., but also has a wider range of application scenarios due to its unique shape and structural design. Heat shrinkable laminated bags are usually used to package items of various shapes and sizes, such as food, electronic products, mechanical parts, etc. Through heating and shrinkage, the bag can tightly wrap the items and provide effective protection and fixation. In the current packaging market, heat shrinkable laminated films and bags are widely used in the packaging of various products.
[0004] However, traditional laminated films and bags have many shortcomings when facing some specific needs. On the one hand, for products such as food and medicine that are sensitive to oxygen and water vapor, the barrier performance of traditional laminated films is limited, and it is difficult to effectively prevent the penetration of oxygen and water vapor, resulting in a shortened shelf life of the product. On the other hand, when packaging fragile items such as glass products and electronic products, traditional laminated films lack effective buffering protection, and the products are easily damaged by external impact during transportation and storage. Therefore, it is necessary to propose a heat-shrinkable laminated film and bag to solve the problems in the prior art. Summary of the invention
[0005] The purpose of the present invention is to make up for the shortcomings of the prior art and to provide a heat-shrinkable laminated film and bag, which can improve the protection performance of the packaging contents, extend the shelf life, effectively prevent the penetration of oxygen and water vapor and damage to the product caused by external impact, provide good buffering protection for fragile items, and reduce the probability of damage during transportation and storage.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a heat-shrinkable laminated film, comprising an outer protective layer, an intermediate barrier layer, an inner heat-sealing layer and a buffer layer located on the side close to the package contents, the intermediate barrier layer is formed by laminating a new polyester material modified by nanotechnology and a traditional polyethylene material, and the buffer layer is made of an elastic polyurethane material;
[0007] The novel polyester material is prepared by uniformly dispersing functional nanoparticles in the polyester material, wherein the functional nanoparticles include but are not limited to silicon dioxide nanoparticles, montmorillonite nanoparticles and aluminum oxide nanoparticles, and the nanoparticles are surface treated to improve the dispersibility and compatibility in the polyester material;
[0008] The outer protective layer is made of high-strength polymer material, which has good wear resistance, corrosion resistance and UV resistance;
[0009] The inner heat-sealing layer is made of a material with good heat-sealing performance.
[0010] Furthermore, the novel polyester material and the polyethylene material are layered by co-extrusion technology, and during the co-extrusion process, the temperature is controlled at 190° C.-210° C., the pressure is controlled at 12 MPa-14 MPa, and the extrusion speed is controlled at 6 m / min-7 m / min.
[0011] Furthermore, the polyurethane material of the buffer layer is foamed by a physical foaming method so that it has excellent elasticity and resilience. When the polyurethane material is physically foamed, supercritical carbon dioxide is used as a foaming agent, and the polyurethane raw material and supercritical carbon dioxide are mixed in an autoclave. The pressure is controlled at 7-10MPa and the temperature is 30°C-50°C. Then, the carbon dioxide forms bubbles in the polyurethane material by rapid pressure reduction. The thickness of the buffer layer is between 0.8mm-1.8mm, which is adjusted according to different product requirements. For products with a higher degree of fragility such as packaged glass products, the thickness of the buffer layer is increased to 1.6mm-1.8mm, and for products that are not fragile, the thickness of the buffer layer is adjusted to 0.8mm-1.2mm.
[0012] Furthermore, the steps of preparing the novel polyester material include:
[0013] First, the functional nanoparticles are surface treated, and the nanoparticles are coated with polyoxyethylene-polyoxypropylene-polyoxyethylene. The treatment time is 2 hours to 3 hours, and the treatment temperature is 60° C. to 80° C. The nanoparticles and polyoxyethylene-polyoxypropylene-polyoxyethylene are dispersed in water at a mass ratio of 1:0.5 to 1:1.5. The hydrophilic groups of the polyoxyethylene-polyoxypropylene-polyoxyethylene interact with water, and the hydrophobic groups interact with the surface of the nanoparticles and are coated on the surface of the nanoparticles. Then, the surface of the nanoparticles is coated with a layer of polyoxyethylene-polyoxypropylene-polyoxyethylene by evaporating the solvent, thereby improving the dispersion state of the nanoparticles in the polyester material.
[0014] Then, the surface-treated functional nanoparticles and the polyester resin are added into a twin-screw extruder at a mass ratio of 1:12-1:18, and melt blended at a temperature of 245° C.-255° C., a screw speed of 110 r / min-140 r / min, and a feeding rate of 22 kg / h-28 kg / h for 1.5 hours-2.5 hours;
[0015] Finally, the new polyester material is prepared through extrusion and granulation processes, the extrusion temperature is 230°C-240°C, and the granulation size is 3mm-5mm in diameter.
[0016] Furthermore, the high-strength polymer material of the outer protective layer is polycarbonate and polyamide, with a thickness between 0.15mm-0.25mm, a wear resistance of not less than 500 turns, a corrosion resistance of not less than 95%, and an anti-ultraviolet performance that can effectively block 280nm-400nm ultraviolet rays.
[0017] Furthermore, the heat-sealing material used for the inner heat-sealing layer is polyethylene and polypropylene, the heat-sealing temperature is 130° C.-145° C., and the heat-sealing strength is not less than 15N / 15mm.
[0018] Furthermore, the shrinkage rate of the heat-shrinkable laminated film during the heat shrinkage process is controlled between 35% and 45%, and the heat shrinkage temperature range is 85° C. to 95° C.
[0019] Furthermore, during the preparation process, each layer of material is pretreated, including drying the polyethylene material at a drying temperature of 70°C-80°C for 3 hours-4 hours, and pre-foaming the polyurethane material at a pre-foaming multiple of 3 to 5 times.
[0020] A heat shrinkable laminated bag is made from the above-mentioned heat shrinkable laminated film.
[0021] Furthermore, the heat shrinkable laminated bag is made by cutting and heat sealing the heat shrinkable laminated film, and the heat sealing process adopts a hot pressing sealing method. During the hot pressing sealing, the temperature is controlled at 170°C, the pressure is 10MPa, and the hot pressing time is 5 seconds. The sealing strength of the bag mouth after hot pressing is not less than 20N / 15mm. The size of the heat shrinkable laminated bag is customized according to the needs of the packaging product, and its length range is 10cm-50cm, and its width range is 8cm-40cm. For heat shrinkable laminated bags of different specifications, during the heat shrinking process, the temperature, wind speed and conveying speed of the heat shrinking equipment are adjusted accordingly. When the size of the heat shrinkable laminated bag is small, the temperature of the heat shrinking equipment is set at 88°C, the wind speed is 2m / s, and the conveying speed is 3m / min. When the size of the heat shrinkable laminated bag is large, the temperature of the heat shrinking equipment is set at 92°C, the wind speed is 3m / s, and the conveying speed is 2m / min.
[0022] Compared with the prior art, the heat shrinkable laminated film and bag have the following beneficial effects:
[0023] The invention significantly improves the protective performance of the package contents and prolongs the shelf life. Through the synergistic effect of the high barrier performance of the new polyester material and the polyurethane buffer layer, the polyester material is added with functional nanoparticles through nanotechnology. These nanoparticles have unique physical and chemical properties and can significantly enhance the barrier performance of the polyester material to oxygen, water vapor, etc., effectively preventing the penetration of oxygen and water vapor and damage to the product by external impact, providing all-round protection for the product, and is particularly suitable for packaging fragile items, reducing the risk of damage. The setting of the buffer layer provides good buffering protection for fragile items and reduces the probability of damage during transportation and storage.
[0024] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 It is a schematic diagram of the structure of a heat shrinkable laminated film.
[0027] In the figure: 1. Outer protective layer; 2. Middle barrier layer; 3. Inner heat sealing layer; 4. Buffer layer. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The present invention will be further described below in conjunction with the embodiments.
[0030] Embodiment 1
[0031] Firstly, in the preparation of the new polyester material, montmorillonite nanoparticles were carefully selected as functional nanoparticles, and the nanoparticles and polyoxyethylene-polyoxypropylene-polyoxyethylene (P123) triblock copolymer surfactant were fully dispersed in water at a mass ratio of 1:0.8. In this process, the hydrophilic groups of polyoxyethylene-polyoxypropylene-polyoxyethylene were closely combined with water, while the hydrophobic groups were gently coated on the surface of the nanoparticles. Subsequently, the surface of the nanoparticles was firmly coated with a layer of polyoxyethylene-polyoxypropylene-polyoxyethylene by evaporating the solvent. Then, the surface-treated nanoparticles and polyester resin were added to an advanced twin-screw extruder at a mass ratio of 1:16. Under the precise conditions of a temperature of 248°C, a screw speed of 130r / min, and a feed rate of 24kg / h, melt blending was carried out for up to 2.2 hours. Finally, the new polyester material was successfully prepared through an extrusion process with an extrusion temperature of 238°C and a specific granulation process, with a granulation size of 4.5mm in diameter.
[0032] In the preparation of each layer of the laminated film, the outer protective layer is made of high-quality polyamide material with a thickness of 0.22mm. This material exhibits excellent wear resistance, corrosion resistance and UV resistance, and can effectively block 280nm-400nm ultraviolet rays, providing solid protection for the internal structure. The middle barrier layer uses advanced co-extrusion technology to tightly laminate the new polyester material with the traditional polyethylene material. During the co-extrusion process, the temperature is strictly controlled to 205℃, the pressure is 13.5MPa, and the extrusion speed is 6.8m / min to ensure that the layers of materials are firmly and evenly bonded and give full play to their barrier properties. The inner heat-sealing layer is made of polyamide. Propylene material, heat sealing temperature is set to 138 ℃, heat sealing strength is not less than 16N / 15mm, to ensure the bag mouth is firmly sealed, the buffer layer is made of polyurethane material, and is carefully processed by physical foaming. The polyurethane raw material and supercritical carbon dioxide are mixed in an autoclave, the pressure is controlled at 9MPa, the temperature is 45 ℃, and then the pressure is quickly reduced to make the supercritical carbon dioxide form uniform bubbles in the polyurethane material. For fragile products such as glass products, the buffer layer thickness is adjusted to 1.75mm to provide strong buffer protection. For relatively non-fragile products, the buffer layer thickness is 1.1mm, realizing the rational use of materials.
[0033] Afterwards, the polyethylene material was carefully dried at a temperature of 78°C and a drying time of 3.8 hours. At the same time, the polyurethane material was pre-foamed at a pre-foaming multiple of 4.5 times to further optimize the material properties.
[0034] Finally, when making heat-shrinkable laminated bags, the heat-shrinkable laminated films are precisely cut according to the specific needs of the packaging products, and the laminated bags are made by hot pressing and sealing. During hot pressing and sealing, the temperature is strictly controlled at 172°C, the pressure is 10.5MPa, and the hot pressing time is 5.5 seconds to ensure that the sealing strength of the bag mouth after hot pressing and sealing is not less than 21N / 15mm. When the heat-shrinkable laminated bag is small in size (length less than 20cm, width less than 15cm), the heat shrinking equipment temperature is set to 89°C, the wind speed is 2.2m / s, and the conveying speed is 2.8m / min; when the heat-shrinkable laminated bag is large in size (length greater than 30cm, width greater than 25cm), the heat shrinking equipment temperature is set to 93°C, the wind speed is 3.2m / s, and the conveying speed is 1.8m / min to achieve the best heat shrinking effect.
[0035] This embodiment uses polyamide as the outer protective layer material, which may have better corrosion resistance and wear resistance. Montmorillonite nanoparticles and a specific ratio of polyoxyethylene-polyoxypropylene-polyoxyethylene have unique performance in barrier properties.
[0036] Embodiment 2
[0037] In the first step of preparing the new polyester material, silica nanoparticles are selected as functional nanoparticles, and the nanoparticles and P123 are fully stirred and dispersed in water at a mass ratio of 1:1.2. After evaporation of the solvent, the nanoparticles and polyester resin are carefully added into a twin-screw extruder at a mass ratio of 1:14. The melt blending is carried out for 1.8 hours at a temperature of 252°C, a screw speed of 115r / min, and a feed rate of 26kg / h. The extrusion temperature is 232°C, and a granulation size of 3.5mm in diameter is obtained through a specific granulation process.
[0038] During the preparation of each layer of the laminated film, the outer protective layer is made of polycarbonate material with a thickness of 0.18mm. This material has good wear resistance, corrosion resistance and UV resistance, and can effectively block 280nm-400nm ultraviolet rays. The middle barrier layer uses co-extrusion technology to laminate the new polyester material with the traditional polyethylene material. During the co-extrusion process, the temperature is controlled at 195°C, the pressure is 12.5MPa, and the extrusion speed is 6.2m / min. The inner heat-sealing layer is made of polyethylene material, the heat-sealing temperature is 132°C, and the heat-sealing strength is not less than 15.5N / 15mm. The buffer layer is made of polyurethane material and is processed by physical foaming. The polyurethane raw material and supercritical carbon dioxide are mixed in an autoclave. The pressure is controlled at 7.5MPa and the temperature is 35°C. For fragile products such as glass products, the buffer layer thickness is 1.65mm, and for relatively non-fragile products, the buffer layer thickness is 0.9mm.
[0039] When the polyethylene material is dried, the drying temperature is set to 72° C. and the drying time is set to 3.2 hours. The polyurethane material is pre-foamed and the pre-foaming multiple is 3.5 times.
[0040] When making heat-shrinkable laminated bags, heat compression sealing is adopted. During heat compression sealing, the temperature is controlled at 168°C, the pressure is 9.5MPa, and the heat compression time is 4.5 seconds to ensure that the sealing strength of the bag mouth after heat compression sealing is not less than 19N / 15mm. When the heat-shrinkable laminated bag is small in size (length less than 20cm, width less than 15cm), the temperature of the heat shrinking equipment is set to 87°C, the wind speed is 1.8m / s, and the conveying speed is 3.2m / min. When the heat-shrinkable laminated bag is large in size (length greater than 30cm, width greater than 25cm), the temperature of the heat shrinking equipment is set to 91°C, the wind speed is 2.8m / s, and the conveying speed is 2.2m / min.
[0041] This embodiment uses polycarbonate as the outer protective layer, which may have advantages in anti-ultraviolet performance. The silicon dioxide nanoparticles and different polyoxyethylene-polyoxypropylene-polyoxyethylene ratios make the material performance unique.
[0042] Embodiment 3
[0043] When preparing the new polyester material, a mixture of silica nanoparticles and montmorillonite nanoparticles was selected as the functional nanoparticles. The nanoparticles and polyoxyethylene-polyoxypropylene-polyoxyethylene were uniformly dispersed in water at a mass ratio of 1:1. After evaporation of the solvent, the nanoparticles and polyester resin were added to a twin-screw extruder at a mass ratio of 1:17. The melt blending was carried out for 2 hours at a temperature of 255°C, a screw speed of 125r / min, and a feed rate of 27kg / h. The extrusion temperature was 235°C and the granulation size was 4mm in diameter.
[0044] In the preparation of each layer of the laminated film, the outer protective layer is made of polyamide material with a thickness of 0.2mm. This material has excellent wear resistance, corrosion resistance and UV resistance, and can effectively block 280nm-400nm ultraviolet rays. The middle barrier layer uses co-extrusion technology to laminate the new polyester material with the traditional polyethylene material. During the co-extrusion process, the temperature is controlled at 208°C, the pressure is 14MPa, and the extrusion speed is 7m / min. The inner heat-sealing layer is made of polypropylene material with a heat-sealing temperature of 140°C and a heat-sealing strength of not less than 17N / 15mm. The buffer layer is made of polyurethane material and is processed by physical foaming. The polyurethane raw material and supercritical carbon dioxide are mixed in an autoclave. The pressure is controlled at 9.5MPa and the temperature is 48°C. For fragile products such as glass products, the buffer layer thickness is 1.8mm, and for relatively non-fragile products, the buffer layer thickness is 1mm.
[0045] The polyethylene material was dried at a temperature of 79° C. for 3.9 hours, and the polyurethane material was pre-foamed at a pre-foaming multiple of 4.8 times.
[0046] When making heat-shrinkable laminated bags, heat compression sealing is adopted. During heat compression sealing, the temperature is controlled at 175°C, the pressure is 11MPa, and the heat pressing time is 6 seconds to ensure that the sealing strength of the bag mouth after heat compression sealing is not less than 22N / 15mm. When the size of the heat-shrinkable laminated bag is small (length less than 20cm, width less than 15cm), the temperature of the heat shrinking equipment is set to 90°C, the wind speed is 2.5m / s, and the conveying speed is 2.5m / min. When the size of the heat-shrinkable laminated bag is large (length greater than 30cm, width greater than 25cm), the temperature of the heat shrinking equipment is set to 94°C, the wind speed is 3.5m / s, and the conveying speed is 1.5m / min.
[0047] This embodiment uses a mixture of silicon dioxide and montmorillonite nanoparticles, which can combine the advantages of both in terms of barrier performance. Polyamide is used as the outer protective layer, which is suitable for products with higher packaging requirements.
[0048] Embodiment 4
[0049] First, for the preparation of the new polyester material, aluminum oxide nanoparticles were selected as functional nanoparticles, and the nanoparticles and a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer surfactant were dispersed in water at a mass ratio of 1:0.9, and a layer of polyoxyethylene-polyoxypropylene-polyoxyethylene was coated on the surface of the nanoparticles by evaporating the solvent. Then, the surface-treated nanoparticles and the polyester resin were added to a twin-screw extruder at a mass ratio of 1:15.5, and melt-blended for 2 hours at a temperature of 250°C, a screw speed of 120r / min, and a feeding rate of 25.5kg / h. Finally, the new polyester material was prepared by an extrusion process with an extrusion temperature of 236°C and a specific granulation process, and the granulation size was 4.2mm in diameter.
[0050] Next, the preparation of each layer of the laminated film is carried out. The outer protective layer is made of a composite material of polycarbonate and polyamide with a thickness of 0.21mm. It has good wear resistance, corrosion resistance and UV resistance, and can effectively block 280nm-400nm ultraviolet rays. The middle barrier layer is laminated with a new polyester material and a traditional polyethylene material through co-extrusion technology. During the co-extrusion process, the temperature is controlled at 202°C, the pressure is 13MPa, and the extrusion speed is 6.6m / min to ensure that the layers of materials are firmly and evenly bonded. The inner heat-sealing layer is made of a mixture of polyethylene and polypropylene. The heat-sealing temperature is 136°C, and the heat-sealing strength is not less than 16.5N / 15mm. The buffer layer is made of polyurethane material and is processed by physical foaming. The polyurethane raw material and supercritical carbon dioxide are mixed in an autoclave. The pressure is controlled at 8.5MPa and the temperature is 42°C. For fragile products such as glass products, the thickness of the buffer layer is 1.72mm; for relatively non-fragile products, the thickness of the buffer layer is 1.05mm.
[0051] Then, the polyethylene material was dried at a temperature of 76° C. for 3.6 hours, and the polyurethane material was pre-foamed at a pre-foaming multiple of 4.2 times.
[0052] Finally, heat shrinkable laminated bags are made. According to the needs of packaging products, the heat shrinkable laminated films are cut and the laminated bags are made by hot pressing and sealing. During hot pressing and sealing, the temperature is controlled at 171°C, the pressure is 10.2MPa, and the hot pressing time is 5.2 seconds. The sealing strength of the bag mouth after hot pressing and sealing is not less than 20.5N / 15mm. When the size of the heat shrinkable laminated bag is small (length less than 20cm, width less than 15cm), the temperature of the heat shrinking equipment is set to 88.5°C, the wind speed is 2.1m / s, and the conveying speed is 2.7m / min. When the size of the heat shrinkable laminated bag is large (length greater than 30cm, width greater than 25cm), the temperature of the heat shrinking equipment is set to 92.5°C, the wind speed is 3.1m / s, and the conveying speed is 1.9m / min.
[0053] This embodiment uses a polycarbonate and polyamide composite material as the outer protective layer, combining the advantages of both, and may be better in wear resistance, corrosion resistance and UV resistance. Alumina nanoparticles and a specific proportion of polyoxyethylene-polyoxypropylene-polyoxyethylene may bring different performances. The inner heat-sealing layer uses a polyethylene and polypropylene mixed material, and the heat-sealing performance may be more stable.
[0054]
[0055]
[0056] In the above table, Example 1 may be better in corrosion resistance and wear resistance, but is not the most outstanding in comprehensive performance. Example 2 uses polycarbonate as the outer protective layer, which has advantages in UV resistance, but may not be as good as Example 1 in corrosion resistance and wear resistance, and has certain limitations in comprehensive performance. Example 3 uses a mixture of silica and montmorillonite nanoparticles, which combines the advantages of both in barrier performance. In some performance aspects, it may overemphasize high-end demands, and there may be a problem of high cost for some ordinary packaging needs. Example 4 uses a polycarbonate and polyamide composite material as the outer protective layer, combining the advantages of both, and may be more outstanding in wear resistance, corrosion resistance and UV resistance. The inner heat-sealing layer uses a mixed material of polyethylene and polypropylene, and the heat-sealing performance may be more stable.
[0057] If corrosion resistance, wear resistance and barrier properties are important, and the heat shrinking temperature requirement is moderate, embodiment 1 is a better choice. If the anti-ultraviolet performance requirement is high, and the heat shrinking temperature requirement is relatively low, embodiment 2 is more suitable. For the situation where the packaging requirements are extremely high and the cost factor is not considered, embodiment 3 may be the best, and embodiment 4 is the best in terms of comprehensive performance.
[0058] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the same elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A heat shrinkable laminate film, characterized in that The invention comprises an outer protective layer (1), an intermediate barrier layer (2), an inner heat-sealing layer (3), and a buffer layer (4) located on a side close to the package contents, the intermediate barrier layer (2) being formed by laminating a novel polyester material modified by nanotechnology and a traditional polyethylene material, and the buffer layer (4) being made of an elastic polyurethane material; The novel polyester material is prepared by uniformly dispersing functional nanoparticles in the polyester material, wherein the functional nanoparticles include but are not limited to silicon dioxide nanoparticles, montmorillonite nanoparticles and aluminum oxide nanoparticles, and the nanoparticles are surface treated to improve the dispersibility and compatibility in the polyester material; The outer protective layer (1) is made of a high-strength polymer material, which has good wear resistance, corrosion resistance and UV resistance; The inner heat-sealing layer (3) is made of a material with good heat-sealing properties.
2. A heat shrinkable laminated film according to claim 1, characterized in that: The novel polyester material and the polyethylene material are layered by co-extrusion technology. During the co-extrusion process, the temperature is controlled at 190° C.-210° C., the pressure is controlled at 12 MPa-14 MPa, and the extrusion speed is controlled at 6 m / min-7 m / min.
3. The heat shrinkable laminated film according to claim 1, characterized in that: The polyurethane material of the buffer layer (4) is foamed by a physical foaming method so that it has excellent elasticity and resilience. When the polyurethane material is subjected to physical foaming, supercritical carbon dioxide is used as a foaming agent. The polyurethane raw material and the supercritical carbon dioxide are mixed in an autoclave, the pressure is controlled at 7-10 MPa, the temperature is 30° C.-50° C., and then the carbon dioxide is rapidly reduced in pressure to form bubbles in the polyurethane material. The thickness of the buffer layer (4) is between 0.8 mm and 1.8 mm and is adjusted according to the requirements of different products. For products with a high degree of fragility such as packaged glass products, the thickness of the buffer layer (4) is increased to 1.6 mm-1.8 mm. For products that are not fragile, the thickness of the buffer layer (4) is adjusted to 0.8 mm-1.2 mm.
4. The heat shrinkable laminated film according to claim 1, characterized in that: The steps for preparing the novel polyester material include: First, the functional nanoparticles are surface treated, and the nanoparticles are coated with polyoxyethylene-polyoxypropylene-polyoxyethylene. The treatment time is 2 hours to 3 hours, and the treatment temperature is 60° C. to 80° C. The nanoparticles and polyoxyethylene-polyoxypropylene-polyoxyethylene are dispersed in water at a mass ratio of 1:0.5 to 1:1.
5. The hydrophilic groups of the polyoxyethylene-polyoxypropylene-polyoxyethylene interact with water, and the hydrophobic groups interact with the surface of the nanoparticles and are coated on the surface of the nanoparticles. Then, the surface of the nanoparticles is coated with a layer of polyoxyethylene-polyoxypropylene-polyoxyethylene by evaporating the solvent, thereby improving the dispersion state of the nanoparticles in the polyester material. Then, the surface-treated functional nanoparticles and the polyester resin are added into a twin-screw extruder at a mass ratio of 1:12-1:18, and melt blended at a temperature of 245° C.-255° C., a screw speed of 110 r / min-140 r / min, and a feeding rate of 22 kg / h-28 kg / h for 1.5 hours-2.5 hours; Finally, the new polyester material is prepared through extrusion and granulation processes, the extrusion temperature is 230°C-240°C, and the granulation size is 3mm-5mm in diameter.
5. The heat shrinkable laminated film according to claim 1, characterized in that: The high-strength polymer material of the outer protective layer (1) is polycarbonate and polyamide, with a thickness between 0.15mm and 0.25mm, and has a wear resistance of not less than 500 revolutions, a corrosion resistance of not less than 95%, and an anti-ultraviolet performance that can effectively block 280nm-400nm ultraviolet rays.
6. The heat shrinkable laminated film according to claim 1, characterized in that: The inner heat-sealing layer (3) is made of polyethylene and polypropylene, the heat-sealing temperature is between 130°C and 145°C, and the heat-sealing strength is not less than 15N / 15mm.
7. The heat shrinkable laminated film according to claim 1, characterized in that: The shrinkage rate of the heat-shrinkable laminated film during the heat shrinkage process is controlled between 35% and 45%, and the heat shrinkage temperature range is 85° C. to 95° C.
8. The heat shrinkable laminated film according to claim 1, characterized in that: During the preparation process, each layer of material is pretreated, including drying the polyethylene material at a drying temperature of 70°C-80°C and a drying time of 3 hours-4 hours, and pre-foaming the polyurethane material at a pre-foaming multiple of 3 times-5 times.
9. A heat shrinkable laminate bag, characterized in that: The heat-shrinkable laminated bag is made of the heat-shrinkable laminated film according to any one of claims 1 to 8.
10. The heat shrinkable laminate bag according to claim 1, characterized in that: The heat shrinkable laminated bag is made by cutting and heat sealing the heat shrinkable laminated film, and the heat sealing process adopts a heat pressing sealing method. During the heat pressing sealing, the temperature is controlled at 170°C, the pressure is 10MPa, and the heat pressing time is 5 seconds. The sealing strength of the bag mouth after the heat pressing sealing is not less than 20N / 15mm. The size of the heat shrinkable laminated bag is customized according to the needs of the packaging product, and its length range is 10cm-50cm, and its width range is 8cm-40cm. For heat shrinkable laminated bags of different specifications, during the heat shrinking process, the temperature, wind speed and conveying speed of the heat shrinking equipment are adjusted accordingly. When the size of the heat shrinkable laminated bag is small, the temperature of the heat shrinking equipment is set at 88°C, the wind speed is 2m / s, and the conveying speed is 3m / min. When the size of the heat shrinkable laminated bag is large, the temperature of the heat shrinking equipment is set at 92°C, the wind speed is 3m / s, and the conveying speed is 2m / min.
Citation Information
Patent Citations
Core-shell type La(1-x)SrxMnO3 / Au nanometer composite particle and preparation method thereof
CN103203451A
Environmental-friendly nano-modified degradable material and preparation method thereof
CN104528162A
Heat-sealable high-barrier packaging film
CN106280306A
Heat-shrinkable laminate film and bag
CN108724866A
Polymer composite material with buffering and energy absorbing characteristics and excellent low-temperature performance and preparation method thereof
CN117946513A